2021
DOI: 10.2217/epi-2021-0123
|View full text |Cite
|
Sign up to set email alerts
|

External validation of integrated genetic-epigenetic biomarkers for predicting incident coronary heart disease

Abstract: Aim: The Framingham Risk Score (FRS) and ASCVD Pooled Cohort Equation (PCE) for predicting risk for incident coronary heart disease (CHD) work poorly. To improve risk stratification for CHD, we developed a novel integrated genetic-epigenetic tool. Materials & methods: Using machine learning techniques and datasets from the Framingham Heart Study (FHS) and Intermountain Healthcare (IM), we developed and validated an integrated genetic-epigenetic model for predicting 3-year incident CHD. Results: Our approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…The accuracy, sensitivity and specificity obtained using the random forest classifier were 0.78, 0.75 and 0.80, respectively. In a 2021 study by Meeshanthini V Dogan et al [45], an ensemble genetic performance genetic model for predicting 3-year coronary events was developed. This model showed a sensitivity of 0.79, a specificity of 0.75, a sensitivity of 0.15 and a specificity of 0.93 on the test set.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The accuracy, sensitivity and specificity obtained using the random forest classifier were 0.78, 0.75 and 0.80, respectively. In a 2021 study by Meeshanthini V Dogan et al [45], an ensemble genetic performance genetic model for predicting 3-year coronary events was developed. This model showed a sensitivity of 0.79, a specificity of 0.75, a sensitivity of 0.15 and a specificity of 0.93 on the test set.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…These data were then subjected to the same quality control procedure as the FHS cohort. 3 In total, 862 593 methylation and 818 046 SNP loci survived quality control measures. For the data mining analyses, we retained loci common to both the Illumina Infinium HumanMethylation450 BeadChip array and Illumina Infinium MethylationEpic Beadchip array arrays, resulting in 437 242 loci being available for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In previous work, we have shown that artificial intelligence (AI)‐aided diagnostic approaches incorporating epigenetic (DNA methylation) effects and gene‐methylation interactions (GxMeth) can be translated into clinically implementable methods that can outperform standard lipid‐based approaches in predicting 3‐year risk for the onset of symptomatic CHD. 3 However, whether clinical translation could be successfully achieved for similar in silico findings 4 for the detection of stable CHD has remained uncertain. Instead, current guidelines for assessing the presence of stable CHD stipulate the use of established measures such as the use of nonemergent exercise stress tests with ECGs or coronary computed tomographic angiography, depending on factors such as the degree of clinical suspicion, the ability to exercise, and the likelihood of high‐risk events.…”
mentioning
confidence: 99%
“…Genetic risk factors have become increasingly well-established over the past decade with the increased use of genome-wide association studies (GWAS) to identify disease-susceptibility loci [ 132 , 133 , 134 ]. However, epigenetic diagnostic markers and therapeutic targets, independent of genetic inheritance, have also been identified [ 135 , 136 , 137 ]. While associations between the risk factors and the clinical outcomes are commonly acknowledged, the cascade of events proceeding via cell aging, presenting as overt changes in tissue and organ function, and ultimately as clinical disease, are less well appreciated.…”
Section: Future Approaches To Cardiovascular Disease Interventionmentioning
confidence: 99%